The Effectiveness of Artificial Intelligence and Strategic Planning in Building Mental Modeling to Improve Sports Performance in Karate - Mohamed Asim Ghazi (دراسات وبحوث التربية الرياضية, 2022)
The importance of the study is due to reaching a model using planning and artificial intelligence techniques to the top of performance. Increasing self-confidence and clarity of goals before sports performance and during sports performance, the ability to use strengths and blocking weaknesses from the opponent, controlling and controlling emotional aspects, technical and tactical reading For the opponent’s strengths and weaknesses and adapting the playing style to the circumstances of each match, the study aims to: Identify “how the effectiveness of artificial intelligence and strategic planning on building mental modeling to improve sports performance”, and the researcher used the descriptive applied survey method for its suitability to the nature of the study. The researcher chose the study sample in a random way represented by players (Karate - Taekwondo - Kungfu), and the number of the sample was (5) players from each game, and the total was (15) players, and the conclusions were that the descriptive analysis between combat sports in Table (2) is in sports Karate The average expressive movements from using the visible face on the analysis sensors, the look in the eyes of the opponent, the look according to the situation, the authoritarian look was (2.07)%, and in the sport of Taekwondo (0.69)% and the sport of Kungfu (0.61)%, except for the criteria of the look according to the situation The offensive is different from the other games of karate and taekwondo, and the standards of the authoritarian view have decreased from other games, and the recommendations are the work of mental modeling in other games in different sports.